Isolation of Four Flavanones from the Leaves of Macaranga Hypoleuca (Rchb.f. & Zoll.) Müll.Arg - Muhamad Nazeri, H.; Ahmat, N.; Abdul Khalil, K. (International Journal of Engineering and Technology, 2019)
Macaranga is a large genus belongs to Euphorbiaceae family which commonly distributed in the tropical region of Africa, South-East Asia, China, and India. The plant of this genus contain flavonoids and stilbenes bearing various terpenyl groups including prenyl, geranyl and farnesyl groups. The leaves of M. hypoleuca were collected from reserved forest UiTM Jengka Pahang, Malaysia, and the dried powdered leaves were macerated in methanol at room temperature. The crude methanol extract was subjected to liquid-liquid partition using n-hexane and ethyl acetate to obtain hexane, ethyl acetate and aqueous fractions. The ethyl acetate fraction was semi purified using vacuum liquid chromatography (VLC) to give nine major fractions (MHL1-MHL9). Fraction MHL3 was further purified by column chromatography (CC) and preparative thin layer chromatography (p-TLC) to give two pure compounds, 8-prenylnaringenin (1) and sakuranetin (5,4â€™-dihydroxy-7-methoxyflavanone) (3). Meanwhile, fraction MHL6 was purified using column chromatography (CC) and p-TLC to yield another two pure compounds, 6-(3-hydroxy-3-methyl)naringenin (2) and 7-O-methyleriodictyol (4). The chemical structure of these isolated compounds were determined based on their 1D and 2D NMR, UV, and IR data. From this study, four flavanones were isolated from the leaves of M. hypoleuca.Â Â